Evaluasi Program Kombel dalam Meningkatkan Kompetensi Guru di SD Inpres Naimata - Eder Maufani; Metriana Kamlasi; Yisma Banfatin; Herson Dabadida; Yonatan Foeh (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to evaluate the implementation of the Learning Community Program (Kombel) in improving teacher competence at SD Inpres Naimata using the CIPP evaluation model (Context, Input, Process, Product). A qualitative approach was employed, utilizing in-depth interviews, observations, and document analysis. The context evaluation revealed that Kombel addressed teachers’ real needs for improving instructional quality. Input evaluation showed support from school leadership, active teacher involvement, and funding from the BOS program, despite limited facilities. The process evaluation indicated that Kombel activities were collaborative and reflective. Product evaluation demonstrated enhanced pedagogical and professional competencies among teachers. The findings conclude that the Kombel program positively impacted teaching quality and is recommended for continued development as a sustainable strategy for improving educational quality.